2014
DOI: 10.1080/10888705.2014.980888
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Feeding Schedule Change and the Provision of Forage Material on Hair Eating in a Group of Captive Baboons (Papio hamadryas sp.)

Abstract: Hair eating in nonhuman primates is thought to result from a frustrated appetitive drive produced by an inappropriate diet. To investigate whether hair eating could be reduced through changes in diet, a two-part study was conducted with a group of baboons (Papio hamadryas sp.). The first part involved changing to a twice-daily feeding routine, thus providing prolonged access to an appropriate food source. The other part involved scattering a grain mix to encourage more foraging while maintaining a once-daily f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For Chip, who did the most hair‐plucking, mulberry reduced rates to a level comparable to gorillas on the biscuit‐free diet (Less, Bergl, et al, ), and alfalfa further reduced the behavior. Nevill and Lutz () examined hair consumption by lab‐housed baboons ( P. hamadryas sp.) and found that it was increased by splitting the biscuit diet into two feedings but reduced by providing scattered grains for foraging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Chip, who did the most hair‐plucking, mulberry reduced rates to a level comparable to gorillas on the biscuit‐free diet (Less, Bergl, et al, ), and alfalfa further reduced the behavior. Nevill and Lutz () examined hair consumption by lab‐housed baboons ( P. hamadryas sp.) and found that it was increased by splitting the biscuit diet into two feedings but reduced by providing scattered grains for foraging.…”
Section: Discussionmentioning
confidence: 99%
“…and found that it was increased by splitting the biscuit diet into two feedings but reduced by providing scattered grains for foraging. They suggest that, despite the limited cage space, the scattered grains fulfilled a motivation to search for food, which was greater than the motivation to consume it (Nevill & Lutz, ). The distinction between these two motivations is less clear in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in humans, extreme cases of trichophagia and other forms of pica have been linked to iron‐deficiency anemia, and show comorbidity with psychiatric symptoms such as anxiety and depression (Flessner, Woods, Franklin, Keuthen, & Piacentini, ; Kettaneh et al, ). As most of the reports about NHP trichophagia have focused on captive animals (Butler & Haines, ; Gillin et al, ; Gozalo, Montoya, & Nolan, ; Mejido et al, ; Mook, ; Nevill & Lutz, ; Nolan, Schaffer, & Conti, ), it is not clear whether wild primates regularly engage in this behavior. However, there are several accounts of consumption of other non‐food items, such as soils or clays (Krishnamani & Mahaney, ; Mahaney, Hancock, & Inoue, ; Mahaney et al, ; Pebsworth, Bardi, & Huffman, ; Pebsworth et al, ; Wakibara et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although abnormal behaviors can be uniquely individualistic, for the purpose of this paper they will be classified into four categories: motor stereotypy , which includes behaviors such as pacing, rocking, flipping, swinging, and head tossing (Camus et al, 2013; Fritz et al, 1992; Gottlieb et al, 2015; Hook et al, 2002; Lutz et al, 2003; Nash et al, 1999; Vandeleest et al, 2011); self-directed behaviors which include hair-pulling, “saluting,” eye-covering, or digit sucking (Fritz et al, 1992; Hook et al, 2002; Jacobson et al, 2016; Lutz et al, 2003; Thierry, 1984); abnormal appetitive behavior which includes regurgitation, hair eating, and coprophagy (Akers and Schildkraut, 1985; Birkett and Newton-Fisher, 2011; Fritz et al, 1992; Gould and Bres, 1986; Hook et al, 2002; Jacobson et al, 2016; Nash et al, 1999; Nevill and Lutz, 2015); and self-injurious behavior which includes behaviors that result in injury or have the potential for injury such as head-banging, self-biting, and self-wounding (Birkett and Newton-Fisher, 2011; Gottlieb et al, 2013; Hosey and Skyner, 2007; Lutz et al, 2003; Rommeck et al, 2009). Various factors play a role in the display of abnormal behavior.…”
Section: Introductionmentioning
confidence: 99%
“…For example, captive gorillas ( Gorilla gorilla ) are often reported to exhibit coprophagy and regurgitation/reingestion (Akers and Schildkraut, 1985; Gould and Bres, 1986), while coprophagy tends to be the most common abnormal behavior in chimpanzees ( Pan troglodytes ) (Birkett and Newton-Fisher, 2011; Jacobson et al, 2016; Nash et al, 1999; Walsh et al, 1982). Similarly, hair-pulling and hair-eating is common in baboons (Brent and Hughes, 1997; Mejido et al, 2009; Nevill and Lutz, 2015) and “wiggle digits,” a behavior that is often associated with regurgitation, appears to be limited to the baboon population (Lutz et al, 2014). In contrast, pacing, a motor stereotypy, is a behavior that is commonly performed by many species of captive nonhuman primates (Bellanca and Crockett, 2002; Crast et al, 2014; Lutz et al, 2003, 2014; McGrogan and King, 1982; Pomerantz et al, 2012, 2013; Tarou et al, 2005; Vandeleest et al, 2011).…”
Section: Introductionmentioning
confidence: 99%